Health and safety: the use of pct-based techiques to determine molecular characteristic changes in the enteric pathogens for effective post-flood infection control strategies - Azian, Harun (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2017)
Given the magnitude of the 2014 flood in Kelantan, a great deal of changes are expected namely in the rates and severity of microbial contamination, microbiological profiles of the water sources, and consequently the incidence of infectious diseases associated with contaminated food and water. Immediate humanitarian aids to the flood victims have been widely supplied induding shelter, food, dothing and medications induding oral antibiotics. There was a huge possibility of inappropriate prescription and overexposure of pathogens to antimicrobials, leading to resistance. This study describes the types, proportion, antimicrobial susceptibility profiles and the genetic relatedness of enteric pathogens isolated immediately before and after massive flood in December 2014. Enteric pathogens isolated from stool samples of patients attending Hospital Universiti Sains Malaysia after the flood (January 2015 through June 2015) were collected and compared to pre-flood data. Bacterial identification was perfonmed according to standard method. Serotyping and PCR-based methods were used for specific identification of Salmonella species. Antimicrobial susceptibility testing was perfonmed using disc diffusion method in accordance to CLSI standards. PCR was used for screening of antimicrobial resistance genes and multilocus sequence typing (MLST) was perfonmed to detenmine the genetic relatedness among Salmonella species isolated before and after flood. There was an increment in the isolation of enteric pathogens after flood. Salmonella species were the most frequently isolated enteric pathogens after flood. There was an increment in the isolation of Campyfobacter jejuni and Aeromonas hydrophila. There was higher percentage of resistance to commonly prescribed oral antibiotics such as ciprofloxacin, cefuroxime and erythromycin in post-flood enteric pathogens. Policies need to be delineated to ensure appropriate antimicrobial prescription and usage during future flood response.